Low cholesterol stimulates the nonamyloidogenic pathway by its effect on the α-secretase ADAM 10 - Kojro, Elzbieta (The National Academy of Sciences, 2001)
Biochemical, epidemiological, and genetic findings demonstrate a link between cholesterol levels, processing of the amyloid precursor protein (APP), and Alzheimer's disease. In the present report, we identify the α-secretase ADAM 10 (a disintegrin and metalloprotease) as a major target of the cholesterol effects on APP metabolism. Treatment of various peripheral and neural cell lines with either the cholesterol-extracting agent methyl-β-cyclodextrin or the hydroxymethyl glutaryl-CoA reductase inhibitor lovastatin resulted in a drastic increase of secreted α-secretase cleaved soluble APP. This strong stimulatory effect was in the range obtained with phorbol esters and was further increased in cells overexpressing ADAM 10. In cells overexpressing APP, the increase of α-secretase activity resulted in a decreased secretion of Aβ peptides. Several mechanisms were elucidated as being the basis of enhanced α-secretase activity: increased membrane fluidity and impaired internalization of APP were responsible for the effect observed with methyl-β-cyclodextrin; treatment with lovastatin resulted in higher expression of the α-secretase ADAM 10. Our results demonstrate that cholesterol reduction promotes the nonamyloidogenic α-secretase pathway and the formation of neuroprotective α-secretase cleaved soluble APP by several mechanisms and suggest approaches to prevention of or therapy for Alzheimer's disease.